Rethinking on the interplay of substance abuse and mental health in Indian prisons: a critical analysis - Sruti Bansal; Prachi Motiyani (Discover Mental Health)
Abstract The intricate relationship between substance addiction and mental health among India’s prison population is a formidable task for these institutions. These disorders include psychotic illness, neurotic disorders, substance abuse, personality disorders, and mood disorders. High levels of depression and anxiety, in which substance addiction and mental illness frequently coexist, exacerbate the issue and worsen the outlook for those who are affected. In India, there are many obstacles in the way of inmates with mental health issues facing inappropriate care and inadequate medication administration within the prison system. There are still gaps in the quality of care for people with mental health concerns since the integration of jail health services with the larger National Health Service is still being worked out. A further layer of complexity is created by the proliferation of novel psychoactive substances in prisons, as more research is needed to determine how these drugs affect prisoners mental health. Another area of concern is the disproportionate impact that substance misuse and mental health disorders have on female convicts in India. Research has repeatedly demonstrated that women in prison have greater rates of drug abuse and depression, underscoring the need for assistance and interventions tailored to each gender. One major reason is the inadequate counselling and treatment available in prison which is due to the lack of staff, training and over crowdedness of prisoners. A more thorough and integrated approach is required to solve this complex issue by initiating mental health counselling and treatment plans including de-addiction centres and providing good medical assistance to all irrespective of gender discrimination and barriers to assessing care. This study will highlight the issues that substance abuse causes for prisoners, including how it affects their mental health and will offer various policies and recommendations for the same.